Diagnosis and Management of Tuberculosis Infection in Pregnant Women: A Narrative Review - Noor Hanoush; Lara Abdulmageed; Salahaldin Fahad (Al-Anbar Medical Journal)
Tuberculosis (TB) has been a well-known infectious disease for many centuries. It carries a high rate of morbidity and mortality across the globe. Pregnant women are more susceptible to TB than other individuals owing to the certain physiological changes that accompany pregnancy. There is still doubt that pregnancy is a risk factor for the progression of a TB infection (TBI) to a TB illness. Latent TB infection (LTBI), a term used to describe the fact that mycobacterium tuberculosis is found in a dormant stage, can be isolated in pregnant women. As a rule of thumb, early diagnosis and prompt treatment prevent unwanted complications and even mortality in pregnant women and developing fetuses. As a consequence, knowing the various aspects of TB is of utmost importance when dealing with physicians and pregnant women. Many diagnostic tools, including history and physical examination, chest X-ray, tuberculin test, and interferon-gamma release assays, are useful in the early detection of TB. However, the risks and benefits of each test should be taken into consideration. Furthermore, close monitoring of the pregnant woman with TB is an essential step for early detection of its complications. Anti-tuberculosis therapy, including isoniazid, rifampin, ethambutol, and pyrazinamide, can be used with certain modifications of their doses to decrease the risk of the disease to both a pregnant woman and her fetus. This narrative review aims to summarize the different aspects (epidemiological distribution, risk factors, diagnostic tools, complications, and management) of TB during pregnancy.